THE EFFECTIVENESS OF PAIR WORK IN TEACHING SPEAKING - Fajriani; Patawang, Melda Wahyuni (English Language, Linguistics, and Culture International Journal, 2022)
This research was an attempt to find evidence of the influence of the Pair Work Technique on speaking ability. It was conducted at SMPN 2 Sa’dan with a total of 34 students. This study was carried out by Speaking test and Questionnaire in the classroom. It was conducted in 6 meetings. To determine whether the Pair Work Technique for the teaching of speaking was effective, a speaking test was given at the Experimental group in IX-A class to know the students’ speaking ability. The percentage of the students’ speaking ability in Pre-test, namely; 1) 0% students were got excellent, good, and fair category, 2) the percentage of the poor category was 10% (there are 2 students), 3) the percentage of the very poor category was 90% (there are 18 students). And the percentage of the students’ speaking ability in Post-test, namely: 1) the percentage of the excellent category was 0%, but 2) the percentage of the good category was 10% (there are 2 students), 3) the percentage of the fair category was 85% (there are 17 students), 4) the percentage of the poor category was 5% (just 1 student), 5) the percentage of the very poor category was 0%. While to determine whether the Pair Work Technique for the teaching of speaking was effective, a questionnaire was given in the Experimental group to know the students’ motivation. The percentage of the students’ motivation it was found that: 1) the percentage of the strongly motivated classification was 15% (there are 3 students) 2) the percentage of the motivated classification was 75% (there are 15 students) 3) the percentage of the fairly motivated classification was 10% (there are 2 students). It can be concluded that the Pair Work Technique was effective to improve the students’ speaking ability and students’ motivation for the 9th-grade students of SMPN 2 Sa’dan North Toraja in the academic year 2020/2021.